Synthesis and cholinesterase inhibition of cativic acid derivatives - Alza, Natalia Paola (2014)
Alzheimer’s disease (AD) is a neurodegenerative disorder associated with memory impairment and cognitive deficit. Most of the drugs currently available for the treatment of AD are acetylcholinesterase (AChE) inhibitors. In a preliminary study, significant AChE inhibition was observed for the ethanolic extract of Grindelia ventanensis (IC50 = 0.79 mg/mL). This result prompted us to isolate the active constituent, a normal labdane diterpenoid identified as 17-hydroxycativic acid (1), through a bioassay guided fractionation. Taking into account that 1 showed moderate inhibition of AChE (IC50 = 21.1 lM), selectivity over butyrylcholinesterase (BChE) (IC50 = 171.1 lM) and that it was easily obtained from the plant extract in a very good yield (0.15% w/w), we decided to prepare semisynthetic derivatives of this natural diterpenoid through simple structural modifications. A set of twenty new cativic acid derivatives (3–6) was prepared from 1 through transformations on the carboxylic group at C-15, introducing a C2–C6 linker and a tertiary amine group. They were tested for their inhibitory activity against AChE and BChE and some structure–activity relationships were outlined. The most active derivative was compound 3c, with an IC50 value of 3.2 lM for AChE. Enzyme kinetic studies and docking modeling revealed that this inhibitor targeted both the catalytic active site and the peripheral anionic site of this enzyme. Furthermore, 3c showed significant inhibition of AChE activity in SH-SY5Y human neuroblastoma cells, and was noncytotoxic.